1985
DOI: 10.1002/hep.1840050106
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Gallstone Formation in the Cholesterol–Fed Guinea Pig

Abstract: Female Hartley guinea pigs fed a 0.5% cholesterol-supplemented diet were found to form pigmented gallstones after 6 weeks (17/23) and 12 weeks (11/11), while only 2 of 44 animals fed a trace cholesterol diet formed gallstones over a comparable period. The light brown stones consisted primarily of aggregates of fine granular crystals, morphologically similar to calcium bilirubinate crystals. The stones were soluble in 0.1 N sodium hydroxide and were found to contain a substance which co-migrated with unconjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Dilution of bile without alteration of the relative proportions of cholesterol, bile salts and lecithin does increase the lithogenicity of bile (2). La Morte et al (23) found that cholesterol-fed guinea pigs have greater hepatic bile flow, less absorption of H20 by the gallbladder and greater fasting gallbladder volume than controls.…”
Section: Discussionmentioning
confidence: 98%
“…Dilution of bile without alteration of the relative proportions of cholesterol, bile salts and lecithin does increase the lithogenicity of bile (2). La Morte et al (23) found that cholesterol-fed guinea pigs have greater hepatic bile flow, less absorption of H20 by the gallbladder and greater fasting gallbladder volume than controls.…”
Section: Discussionmentioning
confidence: 98%
“…The lithogenicity of bile decreases following the administration of statins due to a reduction in the total low-density lipoprotein (LDL) cholesterol without affecting the bile acid synthesis as measured by the total bile acid excretion in feces [10]. The effect of a high-cholesterol diet in the formation of pigment stones was documented by an in vivo experiment conducted by Lamorte et al [11]. Guinea pigs fed with a highcholesterol diet formed calcium bilirubinate crystals.…”
Section: Hypercholesterolemia As a Risk Factor For Gallstone Formationmentioning
confidence: 97%
“…H ypertension is an independent risk factor for coronary artery disease 1,2 and for carotid 3,4 and lower extremity 5,6 occlusive disease. Other multivariate clinical studies have shown that pulse pressure is also an independent risk factor for atherosclerosis.…”
mentioning
confidence: 99%